PEMBERDAYAAN PEREMPUAN DAN PENGARUSUTAMAAN GENDER MELALUI LAYANAN PENDIDIKAN MASYRAKAT - Anan Sutisna (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The purpose of this research is to describe woman empowerment and gender equalization through community education service at Community Learning Activity Center in Jakarta. The research which was conducted as from Agust through December 2012 used survey method with descriptive questionnaire and the data were analyzed descriptively . The findings showed (1) the education community service program mostly undertaken by the respondents (61.4%) is gender equalization, and the female respondents of the research is 75.8%, (2) Woman empowerment and gender equalization through community education service is 61.5%. The woman empowerment and gender equalization is regarded as very strategic by integrating various programs designed by the government known as life skills to create good, intelligent, and independent human resources.